Judicial notice: beyond adversarialism and into the exogenous zone. Issue 3 (2nd July 2016) - Hamer, David; Edmond, Gary
ABSTRACT: Recent Australian decisions regarding courts' unilateral access to exogenous (ie non-legal) knowledge have been restrictive, reflecting a strong commitment to the adversarialist principle of party presentation. With reference to underlying goals of factual accuracy, efficient dispute resolution, fairness and institutional integrity we argue that the restrictions should be loosened. The strict principle of party presentation, with only narrow scope for judicial notice, may be justified with regard to the specific facts of the case, given that the parties will have special access to relevant evidence and a strong motivation to present it. However, there is no reason to privilege the parties where legislative facts and general factual propositions are in issue. While the parties should, of course, be given notice and the opportunity to make submissions, the courts should feel an obligation to draw on a wider range of sources of information. This is particularly the case where there is an imbalance in the resources of the parties.